Tying on the mobile apps market and competition rules - Kostecka-Jurczyk, Daria (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The dynamic growth of digital markets is conducive to the use of anti-competitive practices by companies in order to maintain or strengthen their market position. One example of such practices is the abuse of the dominant position occupied by Google, including by tying Android with applications available on Google Play. This tying means that Google imposes on the smartphone manufacturers a “set of applications” necessary to be installed, even if they were not interested in pre-installing some of them. The study analyzes the anti-competitive practices that the European Commission accuses Google of in the decision of 18 August 2018. The purpose of the article is to examine whether tying a specific set of applications with the Android system meets the conditions for abuse of Art. 102 TFEU. This requires, first of all, an examination of whether Android is a binding product for applications available in Google Play and, if so, of whether the conditions of abuse in the form of sales binding are met. As a result, it has been shown that on digital markets, where there is dynamic competition, it is difficult to make an unambiguous assessment of anti-competitive behavior and one of the important arguments that may prejudge the abuse is the harm to end users.
Keywords: abuse of dominant position; competition rules; mobile services markets